Mediatisation and Hyper-commodification of Sport in Post-1980 Turkey - Irak, Dağhan (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Sport has had a symbiotic relationship with television for decades, as it has always been one of the most marketable visual products for the medium. The new visual media technologies that have been introduced since the 1970s have altered this relationship greatly by incrementally commodifying sport at each step. One of the most crucial aspects of this relationship is globalisation, which initially depended on satellite television and took sport’s hyper-commodification to a whole new level. Turkey, which went through a massive transformation to a neoliberal rule following a bloody coup d’etat in 1980 that practically razed the whole social and political structure, has since become an important example of the roles of sport and television in an aggressively neoliberal setting. This chapter aims to explain why televised sport has had a remarkable role in the sociopolitical transformation of Turkey since the 1980 coup.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); Royaume-Uni (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé